Practice and Quality Improvement Leaders Survey of Expectations of DNP Graduates' Quality Improvement Expertise. Issue 6 (November 2021) - Hammersla, Margaret; Belcher, Anne; Ruccio, Lucy Rose; Martin, Jeff; Bingham, Debra
Abstract : Background: Input from practice leaders will improve how doctor of nursing practice (DNP) education is meeting the needs of the employer and improving patient outcomes. Purpose: This article describes the expectations practice leaders have of new DNP graduates' ability to contribute to quality improvement (QI) efforts within health care organizations. Methods: A survey of practice leaders and QI experts investigated the importance and use of QI knowledge and skills. Practice leaders were also asked about the expectations of DNP graduates at the time of hire. Results: The results of this study support the need for nurses pursuing a DNP in advanced nursing practice to have education and training beyond their area of specialization, specifically in QI methods and tools. Conclusions: Faculty need to provide DNP students education that includes concepts in QI and leadership to meet the expectations of future employers and the needs of a complex and changing health care system. Abstract : Supplemental digital content is available in the text.